Models with Endogenous Regressors - Balazsi, L.; Bun, M.; Chan, F.; Harris, Mark N. (Springer, 2017)
This book is aimed at filling this widening gap. The first theoretical part of the volume is providing the econometric foundations to deal with these new high-dimensional panel data sets.